Reactive wetting of high-entropy (La0.2Nd0.2Sm0.2Eu0.2Gd0.2)2Zr2O7 ceramic by molten 71Ag–27Cu–2Ti alloy at 1073–1273 K. Issue 11 (September 2021) - Mao, Hai-Rong; Qiu, Xiao-Ming; Chen, Shuo-Ming; Shen, Ping
Graphical abstract: Highlights: The wettability and interfacial chemistry between high-entropy 5Ln2 Zr2 O7 and Ag–Cu–Ti alloy were explored. The anomalous temperature dependence of the wettability is related to the competitive diffusion of Ti and oxygen ions. The rare-earth cations in the high-entropy ceramic displayed selective interfacial diffusion. The high-entropy 5Ln2 Zr2 O7 ceramic exhibited good wettability with the Ag–Cu–Ti alloy. Abstract: We investigated the wetting of a high-entropy rare-earth oxide, (La0.2 Nd0.2 Sm0.2 Eu0.2 Gd0.2 )2 Zr2 O7, by a molten 71Ag–27Cu–2Ti (in wt%) alloy using a modified sessile drop method at 1073–1273 K. The wettability shows a first increase and then decrease with increasing temperature, depending on the competition among the adsorption and diffusion of active Ti atoms towards triple line, the consumption of Ti due to interfacial reaction and the migration of oxygen from the substrate bulk to the interface. In addition, the La cations in the high-entropy substrate exhibited noticeable outward diffusion while the other rare-earth cations remained stable due to their different bonding strengths in the lattice. Despite the occurrence of interfacial reaction and selective diffusion, the substrate maintained the high-entropy structure after the reactive wetting.